The Role of the Minsk Group in the Nagorno-Karabakh Conflict: Current Crisis and the Importance of Preserving the Existing Mediation Format - Sargsyan, Suren; Muradyan, Anahit; Gevorgyan, Aida; Manoogian, Vahakn (YSU Journal of International Affairs, 2023)
OSCE Minsk Group has been the main mediating body to deal with the Nagorno-Karabakh conflict since 1992. For around 30 years the three Co-Chairs of the Minsk Group- Russia, USA and France, have been productively cooperating on the matter. Minsk Group was believed to be an exclusive forum where the Western and Russian conflicting interests did not hinder the Minsk Group’s mission to provide ways to solve the conflict. However, since the February 2022 Russian-Ukrainian war the cooperation between these countries within the Minsk Group has been largely paralyzed. Unfortunately, this coincided with the aftermath of Nagorno-Karabakh 44-day war in 2020, constant border skirmishes and Azerbaijani aggression and invasion into sovereign territory of the Republic of Armenia. The more internal struggles the Minsk Group experiences, the more regional security suffers. Different actors come up with individual efforts trying to establish themselves as the main mediators between Armenia and Azerbaijan. Under such circumstances there are no balancing mechanisms to restrain the mediating sides from advancing mutually contradicting initiatives which stem from their interests. Hence, this article advocates the importance of the role of the Minsk Group as a body uniting the main mediating actors at the same time being the only body that has the mandate to mediate on issues relating to Nagorno-Karabakh conflict. The article analyzes all the Nagorno-Karabakh conflict resolution plans proposed by the Minsk Group Co-Chairs, the Minsk Group activities during the 2016 and 2020 wars, the stalemate in the negotiations after the 2018 “Velvet revolution” in Armenia as well as the current crisis within the Minsk Group and the importance of preserving the Minsk Group as the main mediating body in the Nagorno-Karabakh conflict.